A one-step synthesis of porous V2O3@C hollow spheres as a high-performance anode for lithium-ion batteries. Issue 53 (18th June 2018) - Wang, Jianbiao; Liu, Zhenwei; Yang, Wenjuan; Han, Lijing; Wei, Mingdeng
Abstract : V2 O3 @C hollow spheres with a large specific surface area exhibited high reversible capacity for LIBs. Abstract : Porous V2 O3 @C hollow spheres composed of ultrathin nanosheets were facilely fabricated via a one-step solvothermal route. When evaluated as an anode material, a large capacity of 583 mA h g −1 can be retained after 800 cycles at a current density of 2 A g −1, exhibiting excellent electrochemical performance.